Quality assessment of urinary stone analysis: results of a multicenter study of laboratories in Europe - Siener, Roswitha; Knoll, Thomas (PLOS ONE, 2016)
After stone removal, accurate analysis of urinary stone composition is the most crucial laboratory diagnostic procedure for the treatment and recurrence prevention in the stone-forming patient. The most common techniques for routine analysis of stones are infrared spectroscopy, X-ray diffraction and chemical analysis. The aim of the present study was to assess the quality of urinary stone analysis of laboratories in Europe. Nine laboratories from eight European countries participated in six quality control surveys for urinary calculi analyses of the Reference Institute for Bioanalytics, Bonn, Germany, between 2010 and 2014. Each participant received the same blinded test samples for stone analysis. A total of 24 samples, comprising pure substances and mixtures of two or three components, were analysed. The evaluation of the quality of the laboratory in the present study was based on the attainment of 75% of the maximum total points, i.e. 99 points. The methods of stone analysis used were infrared spectroscopy (n = 7), chemical analysis (n = 1) and X-ray diffraction (n = 1). In the present study only 56% of the laboratories, four using infrared spectroscopy and one using X-ray diffraction, fulfilled the quality requirements. According to the current standard, chemical analysis is considered to be insufficient for stone analysis, whereas infrared spectroscopy or X-ray diffraction is mandatory. However, the poor results of infrared spectroscopy highlight the importance of equipment, reference spectra and qualification of the staff for an accurate analysis of stone composition. Regular quality control is essential in carrying out routine stone analysis.
Gesehen am 13.12.2019